KARAKTER SISWA PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR SWASTA FULL DAY SCHOOL - Siregar, Nurdiana; Sundari, Dhea; Bakri, Aprilia (AR-RIAYAH : Jurnal Pendidikan Dasar, 2019)
This study aims to: a) describe the character of students in learning mathematics in Private Primary Schools (SDS) full day school, b) knowing the supporting and inhibiting factors in the formation and strengthening of characters in mathematics learning at SDS full day school. This study used qualitative research methods. This research was carried out at SDS IT Siti Hajar. Data collection techniques by observation and interview. Data analysis techniques are data reduction, data display, and conclusion. The results showed that 1) the character of students in mathematics learning included religious, honest, independent, tolerant, hard work, curiosity and responsibility 2) supporting factors for character building in mathematics learning include mathematics teacher, informal learning climate or not rigid, and varied learning methods while the inhibiting factors cannot be implemented in strict class rules in the form of penalties.